PERSEPSI MASYARAKAT KABUPATEN BANJAR TERHADAP PEMANFAATAN ENERGI BIOGAS DAN KUALITAS PUPUK LIMBAH BIOGAS - Danang Biyatmoko; Bayu Wijokongko (Universitas Lambung Mangkurat, 2011)
Research takes place in three villages (Danau Salak, Pengaron, Indrasari). The aims of research are want to know the perception due to build biogas unit (adventage, point plus, obstacle and environment impact), nutrition N, Pand K from solid waste of biogas sludge, and percentage of efficiency fuel that can used by society. Research divided in two steps, first step is want to know the perception of society and the second step is want to know nutrition quality from solid waste from biogas sludge. The first step using Randomized Design method with 4 treatment and 4 replicated. The treatment are kind of raw material used in biogas process, that are : B0 (cattle feces), B1 (chicken feces), B2 (sheep feces) and B3 (duck feces), so needed 16 biogas digesters. Quality nutrition of solid waste of biogas sludge are measured at laboratory.The second step using survey method using 16 respondents from 3 villages and data was analyzed by Kruskal Wallis. Result of the research show, the first step that the difference of raw material (kind of animal feces) not give the real differences on advantages, point plus, obstacle and invironment impact, but the biogas from cattle and sheep feces produce higher efficiency about 41,37% ( 120.000 rupiahs) from chicken and duck feces that produce efficiency only about 20,69% (60.000 rupiahs). The result of second step show the fertilizer from solid waste of biogas sludge that using cattle feces produce the highest nitrogen (N, 1,82% equivalent PK 11,37%) comparing with other treatment, and the best to using as fertilizer .